The neutrophil-to-lymphocyte ratio is an important indicator correlated to early neurological deterioration in single subcortical infarct patients with diabetes - Fang, Lijun; Wang, Yali; Zhang, Hong; Jiang, Lingling; Jin, Xuehong; Gu, Yongquan; Wu, Minya; Pei, Shaofang; Cao, Yongjun (Frontiers in Neurology, 2022)
Background and purpose: This study aimed to investigate the relationship between neutrophil-to-lymphocyte ratio (NLR) and early neurological deterioration (END) among cases suffering from single subcortical infarct (SSI) and diabetes. Methods: We collected the data of SSI patients admitted to our hospital between January 2019 and December 2020 retrospectively. A score of≥2 elevations in overall National Institutes of Health Stroke Scale (NIHSS) score or≥1 increase in motor NIHSS score in 5 days post-admission was considered as END. Furthermore, logistic regression was used to analyze the relationship between NLR and END among SSI cases. Results: Altogether, we enrolled 235 consecutive SSI cases, of which 53 (22.5%) were diagnosed with END while 93 (39.5%) were diabetic. In diabetic patients, the value of NLR increased markedly among the END patients (median, 3.59; IQR, 2.18–4.84) compared to the non-END patients (median, 2.64; IQR, 1.89–3.18; P = 0.032). Meanwhile, in non-diabetic patients, NLR was not significantly associated with END. In the multivariable analysis, NLR values were positively related to END (adjusted odds ratio (OR), 1.768; 95% CI, 1.166–2.682, P = 0.007) upon adjusting age, SSI type, lesion diameter, initial NIHSS, FBG, 2hPBG, and eGFR. The subgroup analysis showed that the relationship between NLR and END was more pronounced in the branch atheromatous disease (BAD) (adjusted odds ratio, 1.819; 95% CI, 1.049–3.153, P = 0.033) and anterior SSI subgroups (adjusted odds ratio, 2.102; 95% CI, 1.095–4.037, P = 0.026). Conclusions: NLR value was significantly related to END among diabetic and SSI patients and was recognized as an independent factor in predicting the risk of END.